Road accident study by using GIS application along FT 2 Kuantan - Maran (KM 1 - KM 57) - Mohd Aizad, Aziz (2012)
Road accidents are one of the major contributors of human deaths in Malaysia In the year 2005, 326,850 accidents were recorded, resulting in an average 17 deaths from road accident every single day. Many highway and traffic agencies have been using Geographic Information System GIS for analyzing accident data. Identification of problematic locations is one of the most important aspects in. accidents studies. The GIS based application combines the information collection capabilities with the visualization. Federal Route 2 from Kuantan to Maran experienced 5605 road accidents between the years 2006 and 2010, killing 122 peoples and injuring 466 peoples. The purpose of this study is to establish road accident database by using GIS which give a quick access for obtaining information based on accident statistic in FT 2 Kuantan - Maran (KM l - KM 57) and to perform prioritization and diagnosis of the blackspot locations along the road and developed of countermeasure of selected blackspot. It was revealed that ArcGIS 9 has proven to be very useful when identifying such zones. The accident statistic from PDRM used as the source for information needed in the database development. The location of the accident was obtained on digitize map. By indication on it, the user can perform queries on particular characteristic to get the accident information.